2011
DOI: 10.1063/1.3544304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of plasma-induced damage to low-k SiOCH films during plasma ashing of organic resists

Abstract: Articles you may be interested inEffects of plasma and vacuum-ultraviolet exposure on the mechanical properties of low-k porous organosilicate glass J. Appl. Phys. 116, 044103 (2014); 10.1063/1.4891501Plasma damage effects on low-k porous organosilicate glass Plasma-induced damage to porous SiOCH ͑p-SiOCH͒ films during organic resist film ashing using dual-frequency capacitively coupled O 2 plasmas was investigated using the pallet for plasma evaluation method developed by our group. The damage was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…Since oxygen plasmas can degrade the low-j dielectric, 299 resist ashing is not performed in an oxygen plasma asher, but rather in a medium-density plasma (e.g., capacitively coupled plasma etcher), using plasmas with lowoxygen concentration or other chemistries, such as N 2 /H 2 based chemistry. Regardless of the ashing process used, some degradation of the dielectric is observed, 299,300 which is substantial for ultra low j (j < 2.3) dielectrics. Therefore, newer dual-damascene schemes such as the trench first metal hard mask (TFMHM) approach attempt to minimize exposure of the low-j dielectric to resist-stripping plasmas.…”
Section: Damascene Structurementioning
confidence: 99%
“…Since oxygen plasmas can degrade the low-j dielectric, 299 resist ashing is not performed in an oxygen plasma asher, but rather in a medium-density plasma (e.g., capacitively coupled plasma etcher), using plasmas with lowoxygen concentration or other chemistries, such as N 2 /H 2 based chemistry. Regardless of the ashing process used, some degradation of the dielectric is observed, 299,300 which is substantial for ultra low j (j < 2.3) dielectrics. Therefore, newer dual-damascene schemes such as the trench first metal hard mask (TFMHM) approach attempt to minimize exposure of the low-j dielectric to resist-stripping plasmas.…”
Section: Damascene Structurementioning
confidence: 99%
“…Fortunately, the chemical structure / bonding of low-k dielectrics is ideally suited for characterization by IR spectroscopy due to the strong IR activity of both the organic component (through various C-H stretching and deformation bands) and the inorganic component (through the Si-O and Si-H stretching bands) [42]. Numerous FTIR, GATR and multiple internal reflection IR (MIRIR) spectroscopy investigations of the chemical modification of low-k dielectrics by various nanofabrication processes have been performed on blanket films [43][44][45][46][47][48][49] and in some cases large periodic arrays of m-nm wide patterned features [26,[50][51][52]. These studies have established general trends and correlations between process chemistries and the low-k dielectric chemical bond structure to the susceptibility of process induced chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that very short plasma exposures can greatly reduce subsequent carbon loss induced by O atoms. Takeda et al showed that ion bombardment can produce a SiO 2 ‐like overlayer, which inhibits O atom penetration in the low‐ k films.…”
Section: Introductionmentioning
confidence: 99%